Agent based simulation of passenger demand for domestic air transport in Iceland - Margrét Jóna Gestsdóttir 1988- (2016)
Reykjavík, the capital city of Iceland, has an airport located in the city centre. The central location of the airport has been debated for decades. The city of Reykjavik has developed plans for the airport to be closed down in the near future i.e. no later than 2024 in order to free up valuable land for development. However, the current location of the airport is very convenient for most users of domestic flights. Transfer of the services to Keflavik Airport, the only existing alternative airport, is expected to decrease significantly the number of passengers using domestic air services due to increased travel time and higher cost. In this thesis an agent based simulation model is created to study the possible changes in flight demand given these changes in the location of the hub domestic airport. In the model, the agents representing travellers on a given route select air or road transportation based on the cost of transport and their time value. The model is calibrated using real data from Flugfélag Íslands for the year 2014 for the busiest domestic air route between Akureyri and Reykjavik. It is subsequently used to evaluate changes in demand for air services on this route under various scenarios which represent the changes associated with a new location of the hub airport. The results show a considerable decrease in demand for domestic air transportation if the domestic flight operation are moved from Reykjavik to Keflavik. The simulation model results indicate that an agent based simulation is a feasible approach to estimate the changes in the demand for services if e.g. domestic flight services were to be transferred to a new location. Also, agent based simulation model can be a valuable tool in helping to understand the behaviour of travellers due to changes in travel time and additional cost of transportation. Keywords: Agent based simulation, flight demand, domestic flight, time value Reykjavíkurflugvöllur er staðsettur stutt frá miðborginni. Staðsetning hans hefur lengi verið til umræðu og verið ...